Improved bone regeneration using bone anabolic drug conjugates (C3 and C6) with deproteinized bovine bone mineral as a carrier in rat mandibular defects. Issue 11 (10th April 2020) - Sheikh, Zeeshan; Abdallah, Mohamed‐Nur; Al‐Jaf, Faik; Chen, Gang; Hamdan, Nader; Young, Robert N.; Grynpas, Marc D.; Glogauer, Michael
Abstract: Background: Deproteinized bovine bone mineral (DBBM) has been extensively studied and used for bone regeneration in oral and maxillofacial surgery. However, it lacks an osteoinductive ability. We developed two novel bone anabolic conjugated drugs, known as C3 and C6, of an inactive bisphosphonate and a bone activating synthetic prostaglandin agonist. The aim was to investigate whether these drugs prebound to DBBM granules have the potential to achieve rapid and enhanced bone regeneration. Methods: Bilateral defects (4.3 mm diameter circular through and through) were created in mandibular angles of 24 Sprague‐Dawley rats were filled with DBBM Control, DBBM with C3 or DBBM with C6 ( n  = 8 defects per group/ each timepoint). After 2 and 4 weeks, postmortem samples were analyzed by microcomputed tomography followed by backscattering electron microscopy and histology. Results: DBBM grafts containing the C3 and C6 conjugated drugs showed significantly more bone formation than DBBM control at 2 and 4 weeks. The C6 containing DBBM demonstrated the highest percentage of new bone formation at 4 weeks. There was no significant difference in the percentage of the remaining graft between the different groups at 2 or 4 weeks. Conclusions: DBBM granules containing conjugated drugs C3 and C6 induced greater new bone volume generated and increased the bone formation rate more than the DBBM controls. This is expected to allow the development of clinical treatments that provide more predictable and improved bone regeneration for bone defect repair in oral and maxillofacial surgery.